2022
DOI: 10.1021/acscentsci.2c00719
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Biantennary N-Glycans Leads to Branch Specific Epitope Recognition by LSECtin

Abstract: The molecular recognition features of LSECtin toward asymmetric N-glycans have been scrutinized by NMR and compared to those occurring in glycan microarrays. A pair of positional glycan isomers (LDN3 and LDN6), a nonelongated GlcNAc4Man3 N-glycan (G0), and the minimum binding epitope (the GlcNAcβ1-2Man disaccharide) have been used to shed light on the preferred binding modes under both experimental conditions. Strikingly, both asymmetric LDN3 and LDN6 N-glycans are recognized by LSECtin with similar affinities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Different techniques measure inherently different properties. It has been pointed out in a recent publication that drastically different outcomes can be obtained from solution to surface experimental approaches and that these variations are highly dependent on the accessibility of the binding motif . The arrangement of glycans and the linker used for immobilization have shown to influence affinity on the glycan array setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different techniques measure inherently different properties. It has been pointed out in a recent publication that drastically different outcomes can be obtained from solution to surface experimental approaches and that these variations are highly dependent on the accessibility of the binding motif . The arrangement of glycans and the linker used for immobilization have shown to influence affinity on the glycan array setting.…”
Section: Resultsmentioning
confidence: 99%
“…The arrangement of glycans and the linker used for immobilization have shown to influence affinity on the glycan array setting. Therefore, it is likely that also the arrangement of a protein on the surface can have a similar effect when the setting is reversed. , The difference in affinities between ITC and BLI for the fungal versus the bacterial lectins may relate to their orientation on the surface. The proteins were immobilized to the surface of a streptavidin-coated sensor through biotinylation of their lysine residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An exception at least in this limited study was WGA, which showed a pronounced linker dependant affinity with up to 14‐fold variation in affinity among different glycoconjugates. A precise explanation for these observations cannot be given as the analysis of binding modes on immobilised substrates is not straightforward and a correlation with solution based binding models is likely to fail [49] . In the absence of molecular techniques for analysing the conformation of surface bound molecules, an explanation of the observed linker dependence remains largely speculative.…”
Section: Discussionmentioning
confidence: 99%
“…A precise explanation for these observations cannot be given as the analysis of binding modes on immobilised substrates is not straightforward and a correlation with solution based binding models is likely to fail. [49] In the absence of molecular techniques for analysing the conformation of surface bound molecules, an explanation of the observed linker dependence remains largely speculative. Altogether our study shows that binding strengths observed at a single lectin concentration, which is a widespread practice for glycan microarray studies, can differ strongly for different linkers and even the calculated surface dissociation constants can very strongly vary for example, for lectins that show different binding modes.…”
Section: Discussionmentioning
confidence: 99%